Investigation of the S-Shaped Current–Voltage Curve in High Open-Circuit Voltage Ruddlesden–Popper Perovskite Solar Cells - Zhong, Hong; Zhou, Renlai; Wu, Xiaoqing; Lin, Xiaoyun; Wang, Ya; Li, Qian; Zhou, Hang (Frontiers in Energy Research, 2021)
We report our investigation on the S-shaped current–voltage characteristics in a hot-casting–processed (BA)2 (MA)3Pb4I13 Ruddlesden–Popper (RP) perovskite solar cell. The two-dimensional perovskite solar cells are fabricated with NiOx as the hole transport layer (HTL), which leads to significantly high open-circuit voltage (Voc). The champion device shows a Voc of 1.21 V and a short current density (Jsc) of 17.14 mA/cm2, leading to an overall power conversion efficiency (PCE) of 13.7%. Although the PCE is much higher than the control device fabricated on PEDOT:PSS, a significant S-shaped current–voltage behavior is observed in these NiOx-based devices. It is found that the S-shaped current–voltage behavior is related to the lower dimensional phase distribution and crystallinity at the bottom interface of the RP perovskite layer, and the S-shaped distortion is less severe after the device ageing test.